In male Hodgkin lymphoma patients, impaired fertility may be improved by non‐gonadotoxic therapy. (31st August 2021) - Laddaga, Filomena Emanuela; Masciopinto, Pierluigi; Nardelli, Claudia; Vacca, Margherita Patrizia; Masciandaro, Paola; Arcuti, Elena; Cicinelli, Ettore; Specchia, Giorgina; Musto, Pellegrino; Gaudio, Francesco
Summary: The outcome of patients with Hodgkin lymphoma (HL) has improved significantly in recent years, and now attention is increasingly being focused on the well‐being of these young patients. This study aimed to analyse the influence of HL and its treatment on the spermatogenic status of 46 male HL patients with available spermiograms, treated between 2008 and 2016. Analysing prognostic factors at diagnosis, we found that the number of spermatozoa was reduced in stage III–IV; motility and vitality were reduced in stage III–IV and in the presence of B symptoms; and abnormal forms were increased in patients with elevated erythrocyte sedimentation rate (ESR) and low albumin. Furthermore, we found that haematopoietic stem cell transplantation (HSCT) was associated with a severe impairment of fertility in terms of sperm motility. In HL‐treated patients who did not undergo HSCT we found a statistically significantly improved fertility in terms of motility. In this study, we found that HSCT induced infertility in the majority of male patients with HL, but that first‐line treatment could improve the impaired fertility status caused by disease. Further studies are needed in larger case series to investigate risk factors for impaired fertility at HL diagnosis and after treatment.